Choosing Between Daily and Event-Driven Pre-exposure Prophylaxis: Results of a Belgian PrEP Demonstration Project. (1st October 2018) - Reyniers, Thijs; Nöstlinger, Christiana; Laga, Marie; De Baetselier, Irith; Crucitti, Tania; Wouters, Kristien; Smekens, Bart; Buyze, Jozefien; Vuylsteke, Bea
Abstract : Background: Daily pre-exposure prophylaxis and event-driven pre-exposure prophylaxis (PrEP) are efficacious in reducing HIV transmission among men who have sex with men (MSM). We analyzed baseline data from a PrEP demonstration project "Be-PrEP-ared" in Antwerp, Belgium, to understand preferences for daily PrEP or event-driven PrEP among MSM at high risk of HIV and factors influencing their initial choice. Methods: Cross-sectional data from an open-label prospective cohort study, using mixed methods. Participants who preregistered online were screened for eligibility and tested for sexually transmitted infections (STIs). Eligible participants chose between daily PrEP and event-driven PrEP and reported on behavioral data through an electronic questionnaire. In-depth interviews were conducted with a selected subsample. Bivariate associations were examined between preferred PrEP regimens and sociodemographic factors, sexual behavior, and STIs at screening. Results: In total, 200 participants were enrolled between October 2015 and December 2016. Self-reported levels of sexual risk-taking before enrollment were high. STI screening revealed that 39.5% had at least 1 bacterial STI. At baseline, 76.5% of participants preferred daily PrEP and 23.5% event-driven PrEP. Feeling able to anticipate HIV risk was the most frequent reason for preferring event-driven PrEP. Regimen choice was associated with sexual risk-taking behavior in the past 3 months. Almost all participants (95.7%) considered it likely that they would change their dosing regimen the following year. Conclusion: Event-driven PrEP was preferred by 23.5% of the participants, which better suits their preventive needs. Event-driven PrEP should be included in PrEP provision as a valuable alternative to daily PrEP for MSM at high risk of HIV.